DNA - Deconstructing Native Affairs: New Equations - Manyaapelo, Jacqueline Kehilwe (Department of Drama, 2020)
This study is an exploration of the articulation of my artistic voice or performance signature. It employs two methodologies, autoethnography and Practice as Research to investigate the practice of my artistic creations as a solo dance-maker. It utilises concepts such as the Batammaliba’s anatomical and metaphorical approach to architecture, Sankofa and decoloniality to frame the investigation. My first solo work, Satisfaction Index, is a point of departure for this analysis. The study then proceeds to engage with works created during the pursuit of this master’s degree over the past two years. In the discovery of my work, DNA and ritual feature to further construct the artistic voice or performance signature that I seek for the articulation of my rebranding as a soloist.